City of glass - Clare, Cassandra (New York Margaret K. McElderry Books, 2010)
Still pursuing a cure for her mother's enchantment, Clary uses all her powers and ingenuity to get into Idris, the forbidden country of the secretive Shadowhunters, and to its capital, the City of Glass, where with the help of a newfound friend, Sebastian, she uncovers important truths about her family's past that will not only help save her mother but all those that she holds most dear
Includes excerpt from the fourth book in the author's Mortal instruments series, City of fallen angels
Includes sneak peek of the first book in the author's Infernal devices trilogy, the prequel to the Mortal instruments series
1
NEW, LITERATURE
Keywords: Demonology -- Juvenile fiction; Families -- History -- Juvenile fiction; Imaginary places -- Juvenile fiction; Magic -- Juvenile fiction; Mothers and daughters -- Juvenile fiction; Paranormal fiction; Vampires -- Juvenile fiction; Young adult fiction; New York (N.Y.) -- Juvenile fiction; Horror fiction; Young adult fiction